Treatment of human pre-B acute lymphoblastic leukemia with the Aurora kinase inhibitor PHA-739358 (Danusertib) - Fei, Fei (BioMed Central, 2012)
BACKGROUND: Treatment of Philadelphia chromosome-positive acute lymphoblastic leukemias (Ph-positive ALL) with clinically approved inhibitors of the Bcr/Abl tyrosine kinase frequently results in the emergence of a leukemic clone carrying the T315I mutation in Bcr/Abl, which confers resistance to these drugs. PHA-739358, an Aurora kinase inhibitor, was reported to inhibit the Bcr/Abl T315I mutant in CML cells but no preclinical studies have examined this in detail in human ALL. RESULTS: We compared the sensitivity of human Bcr/Abl T315I, Bcr/Abl wild type and non-Bcr/Abl ALL cells to this drug. PHA-739358 inhibited proliferation and induced apoptosis independently of Bcr/Abl, the T315I mutation, or presence of the tumor suppressor p53, but the degree of effectiveness varied between different ALL samples. Since short-term treatment with a single dose of drug only transiently inhibited proliferation, we tested combination treatments of PHA-739358 with the farnesyltransferase inhibitor Lonafarnib, with vincristine and with dasatinib. All combinations reduced viability and cell numbers compared to treatment with a single drug. Clonogenic assays showed that 25 nM PHA-739358 significantly reduced the colony growth potential of Ph-positive ALL cells, and combined treatment with a second drug abrogated colony growth in this assay. PHA-739358 further effectively blocked Bcr/Abl tyrosine kinase activity and Aurora kinase B in vivo, and mice transplanted with human Bcr/Abl T315I ALL cells treated with a 3x 7-day cycle of PHA-739358 as mono-treatment had significantly longer survival. CONCLUSIONS: PHA-739358 represents an alternative drug for the treatment of both Ph-positive and negative ALL, although combined treatment with a second drug may be needed to eradicate the leukemic cells.